Reducing Barriers to Women in Academic STEM Fields: Strategies for Institutional Transformation. - Doty, Heather; Andreasen, Robin; Vican, Shawna (Transactions of the American Philosophical Society, 2025)
The article discusses the underrepresentation of women in academic STEM (science, technology, engineering, mathematics) fields in the United States and outlines strategies for institutional transformation to address this issue. Despite women earning over half of U.S. bachelor’s degrees, they represent only 27% of the STEM workforce and face various barriers, including lack of role models, mentoring, and structural support. The National Science Foundation's ADVANCE program, particularly its Institutional Transformation (NSF-IT) grants, aimed to improve gender equity by funding projects that address institutional policies and practices. The article highlights the importance of data-driven approaches and the need for ongoing support and adaptation of initiatives to sustain progress in promoting women's participation in STEM.